2014
DOI: 10.19026/rjaset.7.258
|View full text |Cite
|
Sign up to set email alerts
|

Performance Comparison of New Combinations of Acids with Mud Acid in Sandstone Acidizing

Abstract: The aim of this research is to find the best suitable acid to acidize undamaged low permeable sandstone formation Stimulation of sandstone formations is a challenging task, which involves several chemicals and physical interactions of the acid with the formation. Mud acid has been successfully used to stimulate sandstone reservoirs for a number of years. Matrix acidizing may also be used to increase formation permeability in undamaged wells. The change may be up to 50 to 100% with the mud acid. For any acidizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…production or recovery of hydrocarbons from depleted wells. In this practice, hydrochloric acid solution in the concentration range of 15-32% (depending on whether the formation rock is made of sandstone or limestone) is force down a well bore to etch the formation rocks and create larger flow channels [1][2][3][4]. As it is known, HCl is corrosive hence corrosion of oil well metallic structures is inevitable.…”
mentioning
confidence: 99%
“…production or recovery of hydrocarbons from depleted wells. In this practice, hydrochloric acid solution in the concentration range of 15-32% (depending on whether the formation rock is made of sandstone or limestone) is force down a well bore to etch the formation rocks and create larger flow channels [1][2][3][4]. As it is known, HCl is corrosive hence corrosion of oil well metallic structures is inevitable.…”
mentioning
confidence: 99%
“…The research group in recent years led by Shafiq et al presented multiple experimentations using various acid combinations (Shafiq et al 2013b(Shafiq et al , 2014Shafiq and Shuker 2013;Shafiq et al 2015;Shafiq and Ben Mahmud 2016). The acid combinations tested by the authors included a mixture of orthophosphoric (H 3 PO 4 ) acid and HF; fluoroboric (HBF 4 ) acid and HCOOH; and HCOOH and HF.…”
Section: Retarded Acids and Organic Acidsmentioning
confidence: 99%
“…In comparison with mud acid, phosphonic-based HF acid system shows significantly better performance of permeability enhancement of 177.86% at 300°F. Shafiq et al (2015), Shafiq and Mahmud (2016) and Shafiq et al (2014) performed experimental study with The Berea sandstone core samples were reacted with these acid combinations and analyzed in terms of the porosity, permeability, mineralogy, pH change and strength. According to the findings, although all these acid combinations can be used as the main acid in sandstone acidizing, yet the best acid combination is 3%HF:9%H 3 PO 4 .…”
Section: Fast Reactionmentioning
confidence: 99%
“…These acids also possessed some problems similar to mud acid like fast reaction rates and formation of precipitates. , Shafiq et al (2014) used organic mud acid to acidize sandstone formation in comparison with mud acid and presented their results in terms of acid pH value change. The results revealed that the pH value change after the acidizing is not much when organic mud acid is used as compared to standard mud acid, and this change is even less when fluoboric acid was added in place of hydrofluoric acid.…”
Section: Organic-hf Systemmentioning
confidence: 99%